The treatment of carcinoma in situ and squamous cell carcinoma of the conjunctiva with fractionated strontium-90 radiation in a population with a high prevalence of HIV. Issue 9 (17th March 2015) - Lecuona, Karin; Stannard, Clare; Hart, Gregory; Rice, James; Cook, Colin; Wetter, Julie; Duffield, Maureen
Abstract : Background: This study explores the safety and efficacy of strontium 90 (Sr-90) brachytherapy as the sole adjuvant therapy for carcinoma in situ (CIS) and squamous cell carcinoma (SCC) of the conjunctiva in a high HIV prevalent area. Methods: This is a retrospective case review of patients treated with 60 Gray Sr-90 brachytherapy in four divided doses after resection with a 2 mm margin and histological confirmation. Cryotherapy or alcohol debridement was not performed at the time of excision due to limited resources. Two plaque sizes, 8.5 mm and 18 mm, were used. Results: Sixty-nine patients were treated and had a median follow-up of 27 months (range 6–127). Thirty-three (47.8%) were HIV-positive. CIS was present in 40.6% and SCC in 59.4%. The surgical margins were positive in 39 (56.5%). Twenty patients (29.0%) were treated with the 18 mm plaque and 49 (71.0%) with the 8.5 mm plaque. Eight (11.6%) patients developed a recurrence at a median of 5 months (range 2–40). Recurrences only occurred in patients treated with the 8.5 mm plaque (p=0.094). There was no significant effect of HIV status, positive margins or staging on the number of recurrences. Treatment side effects were a dry eye in five patients which was successfully managed with topical lubricants, and induced astigmatism of 1 dioptre of cylinder in one patient. Conclusions: Sr-90 brachytherapy is safe and effective in preventing recurrences in ocular surface squamous neoplasia in a high HIV prevalent setting. The 18 mm plaque size is superior to the 8.5 mm plaque size.